CULTURAL TRANSFORMATION OF THE OTTOMAN PERIOD PALACE LANDSCAPE IN ISTANBUL - GÖKER, Parisa (SSD Journal, 2018)
Physical environments that are set up within natural environment bear the traces of the periods in which they existed and the traces of societies which lived in these periods by shaping historical structures and positions of structures to one another, the use of gardens and interior/exterior places, the utilized materials, construction techniques, etc., and they put forward the identities of societies. Cities develop and change in accord with the society’s living needs. Today, historical gardens are damaged due to problems including rapid urbanization, population increase and unplanned structuring, etc. Making roads or enlarging the existing roads especially damages the borders and texture of historical palace gardens both visually and physically. Palace gardens in Istanbul have been subject to these problems and their unique borders have been changed or special quality structural components of palace gardens have been demolished because of the new road works carried out or as a result of structuring The Ottoman period historical palace gardens turned out to be the structures which functioned as the living areas of state administration and the Sultans and reflected the art and architectural cognizance of the period with their unique structures. These palaces, consisting of structural groups, have been the areas where the western influence has been observed since the 19th century conspicuously and as a result, they have been the areas where special designs and compositions were created. In this research, historical development of Çırağan Palace, design features, change and transformation in historical process are examined.